2016
DOI: 10.1021/jacs.5b12491
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering How Pore Formation Causes Strain-Induced Membrane Lysis of Lipid Vesicles

Abstract: Pore formation by membrane-active antimicrobial peptides is a classic strategy of pathogen inactivation through disruption of membrane biochemical gradients. It remains unknown why some membrane-active peptides also inhibit enveloped viruses, which do not depend on biochemical gradients. Here, we employ a label-free biosensing approach based on simultaneous quartz crystal microbalance-dissipation and ellipsometry measurements in order to investigate how a pore-forming, virucidal peptide destabilizes lipid vesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 41 publications
2
40
0
Order By: Relevance
“…1b, bottom). In contrast, liposomes of > 160 nm have low membrane curvatures that are not susceptible to AH peptide-mediated pore formation, thus no lysis occurs 5 . In agreement with the liposome results, tested viruses prone to AH peptide inhibition fall within the disruptive range of liposome size: flaviviruses, 40-60 nm; chikungunya virus, 60-70 nm; bunyaviruses, 90-100 nm; and human immunodeficiency virus, 120 nm.…”
mentioning
confidence: 99%
“…1b, bottom). In contrast, liposomes of > 160 nm have low membrane curvatures that are not susceptible to AH peptide-mediated pore formation, thus no lysis occurs 5 . In agreement with the liposome results, tested viruses prone to AH peptide inhibition fall within the disruptive range of liposome size: flaviviruses, 40-60 nm; chikungunya virus, 60-70 nm; bunyaviruses, 90-100 nm; and human immunodeficiency virus, 120 nm.…”
mentioning
confidence: 99%
“…However, the proposed mechanism does not explain virolytic properties of peptides because enveloped viruses do not depend on biochemical gradients. Jackman et al [29] propose that the lysis of the viral membrane is strain induced. The membrane enveloping the virus core is highly curved imposing substantial stress.…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic analysis of the QCM‐D measurement data indicated that cooperative peptide binding leads to pore formation and vesicle rupture, whereas noncooperative binding does not cause vesicle rupture. Combined measurement approaches involving QCM‐D and ellipsometry experiments have further identified that a critical density of peptide‐induced pores form in a lipid vesicle before rupture occurs . Figure illustrates the experimental strategy to measure the peptide (P)/lipid (L) ratio.…”
Section: Bio‐membrane Nanoarchitectonics With Qcm‐dmentioning
confidence: 99%
“…Combined measurement approaches involving QCM-D and ellipsometrye xperiments have further identified that ac riticald ensity of peptide-induced pores form in al ipid vesicle before ruptureo ccurs. [62] Figure 7i llustrates the experimental strategy to measuret he peptide( P)/lipid (L) ratio. In particular,alipid-based model system composed of substrate-supported adsorbed vesicles was monitored by using simultaneousQCM-D and ellipsometry measurements to investigate the membrane-peptide interaction.…”
Section: Membrane-peptide Interactionsmentioning
confidence: 99%
See 1 more Smart Citation